Pursed lips breathing education for asthma patients in Kebonsari Village, Pekalongan Regency, Indonesia - Kartikasari, Dian; Kurniawati, Trina; Faradisi, Firman (Universitas Muhammadiyah Magelang, 2021)
Asthma is a respiratory system disease characterized by symptoms of coughing, shortness of breath and wheezing. Pursed lips breathing is one of the non-pharmacological measures used to treat asthma recurrence. The patients who followed were 10 people. This community service method was in the form of education using leaflets and power points and was attended by 10 asthma patients. The activity began with a pre-test, delivery of material, and ends with a post-test. The results of this activity revealed an increase in knowledge of asthma patients with good criteria as much as 70% and quite as much as 30%. Thus, Pursed lips breathing can effectively prevent the risk of recurrence in asthma patients.